Perceptions of medical undergraduate students toward biomedical research – A sequential, explanatory, mixed-method study from Puducherry, South India - Gaurang Narayan; Anandaraj Rajagopal; Lopamudra Moharana (Journal of Education and Health Promotion, 2023)
BACKGROUND: Biomedical research is not given adequate attention during undergraduation due to the failure of the medical curriculum to motivate the students to take up research, teach the research methodology, and emphasize the scope of research in the future. Our objective was to study the perceptions of medical undergraduate students toward biomedical research and to explore the facilitators and barriers to biomedical research. MATERIALS AND METHODS: This was an explanatory, sequential, mixed-method study. Consenting medical undergraduate students, irrespective of their previous contribution to research, were interviewed by a pretested questionnaire concerning biomedical research, its barriers, and facilitators. For the qualitative component, two focused group discussions (FGDs) were conducted among students in the nonclinical and clinical phases. Data were analyzed and expressed as percentages. Thematic manual content analysis of the transcribed manuscripts was performed. RESULTS: This study included 553 participants. Only 5.52% had previous experience undertaking research. Self-interest and acquiring deeper knowledge were identified as drivers. Lack of motivation, proper guidance, and training in research methodology was found to be the barrier among 90% of the subjects. The FGD reflected the perceptions of students and variations in their ideologies toward taking up research. CONCLUSION: It becomes important to analyze the factors that promote or avert a student from taking up research. A thorough investigation in this regard will be helpful for future cohorts of medical students and will impact their decisions on taking up research and in seeking a career in research-based fields.